(untitled) (Al-Academy, 2024)
Stalking stories represented one of the main sources in the cinematographic industry because of its exciting scenes and attention-grabbing motion treatments, and this drew the researcher’s attention in defining the topic of the research, which was entitled: (Directing the treatment of chase scenes in the film). American movie, which was based on five theoretical seasons, I have the following formula:The first chapter deals (the methodological framework of the research) and includes a presentation of the topic of the research problem represented by the following question: What is the guiding treatment for the stalking scenes in the American film? And the importance of the topic and the goal that it seeks to achieve as well as the broad limits in which it moves, then the researcher defines the terms.As for the second chapter (the theoretical framework and previous studies), it consists of two topics: The first topic: The chase scenes in cinematic films, the second topic: the work of the visual and audio elements in the chase scenes, and finally the conclusion of the results of what the theoretical framework resulted from in terms of indications and touched on previous studies.Chapter Three: (Research Procedures): In which the researcher deals with the following elements: the research method, the research tool, the research community, the unit of analysis, the instrument verification, the research sample, and the steps related to it. Analyze it. Then analyze the sample.As for the fourth chapter (results and conclusions): the researcher finally wrote the results and conclusions, a list of sources.